A Quasi-Experimental Study on Science Philosophy-Based Biology Teaching: Enhancing Students’ Knowledge, Attitudes, and Behavior Toward Biodiversity Conservation - Cici Nur Azizah; Saefudin Saefudin; Ridwan Ridwan; Puan Helwa Rezha Soraya; Rahmat Fahmi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study aims to explore the impact of integrating the philosophy of science into biology teaching on students' awareness of biodiversity and the conservation of Mentawai medicinal plants. A quasi-experimental design was employed, involving two groups: an experimental group (philosophy of science-based teaching) and a control group (conventional teaching). Data were collected using questionnaires that measured students' knowledge, attitudes, and behaviors toward biodiversity. The analysis revealed that the experimental group demonstrated significant improvements across all indicators compared to the control group. Statistically, the experimental teaching method yielded large effect sizes for environmental knowledge (Cohen's d = 0.80), environmental attitudes (Cohen's d = 0.73), and environmental behaviors (Cohen's d = 1.03), with a p-value < 0.05. Consequently, teaching based on the philosophy of science proved significantly more effective in enhancing students' awareness of biodiversity and the conservation of Mentawai medicinal plants. Based on these findings, integrating the philosophy of science into the biology curriculum is recommended to strengthen students' environmental awareness and conservation efforts for local medicinal plants, thereby contributing positively to a more holistic and sustainable education.